(untitled) (Research, Society and Development, 2024)
The objective of the present research was to evaluate the apparent digestibility of protein, energy and amino acids of protein hydrolysates obtained from by-products of the poultry industry. 125 tilapia were used, distributed in five cylindrical tanks with a conical bottom measuring 450 liters, adapted for feces collection. Five diets were formulated using chromium III oxide as an indicator, one being a reference and four including different poultry hydrolysates: liver hydrolyzate (HF); feather hydrolyzate (HP); viscera hydrolyzate (HV); hydrolyzate of viscera, blood and feathers (HVSP). The apparent digestibility coefficients of crude protein, gross energy, amino acids and digestible nutrients were calculated. The protein CDA shows that HP has the highest protein CDA value of 92.17%, followed by HVPS (91.54%), HV (81.91%) and HF (81.51%). The energy CDA was similar, ranging from 87.01% to 87.03%. Regarding the CDA of essential amino acids, it is observed for HP (96.98%), followed by HV (93.58%), HVSP (92.86%) and HF (86.21%). Among the hydrolysates evaluated, the feather hydrolyzate presented higher protein CDA values, and with higher digestible energy values, however, all hydrolysates are excellent sources of nutrients for fish, with good digestibility of protein, energy and amino acids.